Is cytotoxic chemotherapy for lymphoma currently feasible for patients in Malawi? A debate - Crutchlow, Emma (The Medical Association Of Malawi, 2008)
There is currently no systematic provision for chemotherapy of adult patients with cancer in Malawi. Is the introduction of such a service now feasible in Malawi, and should an individual patient with potentially treatable disease be given chemotherapy in the absence of such a service? The technical, economic and moral issues are discussed here in the form of a debate.